1978
DOI: 10.1021/jf60219a036
|View full text |Cite
|
Sign up to set email alerts
|

Method to determine fenthion and five oxidative metabolites in fat

Abstract: This report reflects the results of research only. Mention of a pesticide in this paper does not constitute a recommendation for use by the USDA nor does it imply registration under FIFRA as amended. Also, mention of a commercial or a proprietary product in this paper does not constitute an endorsement by the USDA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1979
1979
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
(4 reference statements)
0
2
0
Order By: Relevance
“…The residues of fenthion and oxidative metabolites in the fat samples were determined by the method of Wright and Riner (1978). This method is a modification of the method of Bowman and Beroza (1968) which was used to determine residues of these compounds in corn, grass, and milk.…”
Section: Methodsmentioning
confidence: 99%
“…The residues of fenthion and oxidative metabolites in the fat samples were determined by the method of Wright and Riner (1978). This method is a modification of the method of Bowman and Beroza (1968) which was used to determine residues of these compounds in corn, grass, and milk.…”
Section: Methodsmentioning
confidence: 99%
“…Since the first attempts to analyze fenthion and its metabolites in corn, grass, and milk using a gas chromatography (GC) equipped flame photometric detector (FPD) to determine their metabolic pathway, several analytical methods have been reported using a UV detector [18], nitrogen-phosphorous detector (NPD) [15,[19][20][21], and FPD [22]. It was reported that analyzing fenthion sulfoxides by GC is challenging because sulfoxide can easily be oxidized and converted into a sulfone form in the injection port of a gas chromatograph.…”
Section: Introductionmentioning
confidence: 99%